2016
DOI: 10.1186/s41235-016-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

From hands to minds: Gestures promote understanding

Abstract: Gestures serve many roles in communication, learning and understanding both for those who view them and those who create them. Gestures are especially effective when they bear resemblance to the thought they represent, an advantage they have over words. Here, we examine the role of conceptually congruent gestures in deepening understanding of dynamic systems. Understanding the structure of dynamic systems is relatively easy, but understanding the actions of dynamic systems can be challenging. We found that see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…What is being gestured matters as well. Research on a sequence of videotaped gestures showed that watching a tutor give an explanation of a dynamic system accompanied by gestures representing the sequence of actions led to deeper understanding of the system’s operation compared to seeing gestures representing the structure of the parts (Kang & Tversky, 2016 ).…”
Section: Being Activementioning
confidence: 99%
“…What is being gestured matters as well. Research on a sequence of videotaped gestures showed that watching a tutor give an explanation of a dynamic system accompanied by gestures representing the sequence of actions led to deeper understanding of the system’s operation compared to seeing gestures representing the structure of the parts (Kang & Tversky, 2016 ).…”
Section: Being Activementioning
confidence: 99%
“…We already know that hand and arm gestures are crucially important to the communication of actions, with hand gestures in particular shown to be a key component of nonverbal communication (Cartmill, Beilock, & Goldin-Meadow, 2012; Kang & Tversky, 2016) and a significant characteristic of emotion recognition (Dael et al., 2012; Wallbott, 1998). Hand gesture recognition research both in humans (Goldin-Meadow, 1999; Krauss, Chen, & Chawla, 1996; Obermeier, Dolk, & Gunter, 2012) and using human–computer interfaces (Murthy & Jadon, 2009; Wachs, Kölsch, Stern, & Edan, 2011) has demonstrated the importance of decoding such cues for effective communication.…”
Section: Introductionmentioning
confidence: 99%
“…Although, gesture-based interactions are suitable for the interaction in a VE [37], such systems are difficult to design [37]. For a novice VR user, it is often difficult to learn and remember different gestures for interactions [21,38].…”
Section: Discussionmentioning
confidence: 99%